Promotion of diet‐induced obesity and metabolic syndromes by BID is associated with gut microbiota. Issue 12 (15th November 2022) - Yan, Shengmin; Zhou, Jun; Zhang, Hao; Lin, Zhen; Khambu, Bilon; Liu, Gang; Ma, Michelle; Chen, Xiaoyun; Chalasani, Naga; Yin, Xiao‐Ming
Abstract: A growing body of evidence has indicated an expanding functional network of B‐cell lymphoma 2 (BCL‐2) family proteins beyond regulation of cell death and survival. Here, we examined the role and mechanisms of BH3 interacting‐domain death agonist (BID), a pro‐death BCL‐2 family member, in the development of diet‐induced metabolic dysfunction. Mice deficient in bid ( bid −/− ) were resistant to high‐fat diet (HFD)–induced obesity, hepatic steatosis, and dyslipidemia with an increased insulin sensitivity. Indirect calorimetry analysis indicated that bid deficiency increased metabolic rate and decreased respiratory exchange ratio, suggesting a larger contribution of lipids to overall energy expenditure. While expression of several genes related to lipid accumulation was only increased in wild‐type livers, metabolomics analysis revealed a consistent reduction in fatty acids but an increase in certain sugars and Krebs cycle intermediates in bid −/− livers. Gut microbiota (GM) analysis indicated that HFD induced gut dysbiosis with differential patterns in wild‐type and in bid −/− mice. Notably, abrogation of GM by antibiotics during HFD feeding eliminated the beneficial effects against obesity and hepatic steatosis conferred by the bid deficiency. Conclusion : These results indicate that the protective role of bid ‐deficiency against diet‐induced metabolic dysfunction interacts with the function of GM. Abstract : 1. Mice deficient in bid were resistant to high‐fat diet‐induced obesity, hepatic steatosis and dyslipidemia with an increased insulin sensitivity. 2. The protective role of bid ‐deficiency against diet‐induced metabolic dysfunction interacts with the function of gut microbiota. 3. BID could affect lipid metabolism as suggested by the findings from gene expression profiling, indirect calorimetry and metabolomics.image